2016
DOI: 10.1088/0169-5983/48/4/045502
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of expansion and compression effects on the stability of Taylor vortex flow

Abstract: The aim of the present experimental work is to determine the stability limits of Taylor cells by expanding and compressing the cells. The investigation was performed under laminar flow condition with a wide gap between an inner rotating cylinder and outer stationary cylinder. In order to allow the expansion and compression of the cells, the test rig was designed with a sliding upper end plate and a fixed lower end plate. The objectives are to determine the maximum and minimum size limits of each number of cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…This phenomenon means that the final pump performance changes according to the steps (history) used to reach the desired conditions, i.e., the flow rates of both phases. Hysteresis can be seen in a variety of flow applications, such as the Taylor vortex flow, where the height and number of vortices strongly depend on how the flow is initiated [49]. Similar to this, for formally identical operating points, large differences in performance can occur in centrifugal pumps when reducing the air flow rate from an initially high value or starting from zero and increasing the air flow rate.…”
Section: Introductionmentioning
confidence: 90%
“…This phenomenon means that the final pump performance changes according to the steps (history) used to reach the desired conditions, i.e., the flow rates of both phases. Hysteresis can be seen in a variety of flow applications, such as the Taylor vortex flow, where the height and number of vortices strongly depend on how the flow is initiated [49]. Similar to this, for formally identical operating points, large differences in performance can occur in centrifugal pumps when reducing the air flow rate from an initially high value or starting from zero and increasing the air flow rate.…”
Section: Introductionmentioning
confidence: 90%
“…Similar phenomena also occur in circular Couette flow with pressure-driven axial flow (Takeuchi & Jankowski 1981; Chung & Astill 1977; Lueptow, Docter & Min 1992) or when fluid is added or withdrawn through a permeable inner cylinder (Min & Lueptow 1994; Tilton & Martinand 2018). It is found that for flow states with fewer than the nominal number of vortices, these vortices are highly stretched in the axial direction and occupy the whole liquid annulus height (Benjamin 1978 a , b ; Martínez-Arias et al 2014; Mansour, Ali & El-Maksoud 2016; Ostilla-Mónico, Lohse & Verzicco 2016). These multiple flow states have recently been found to exist even at extremely high Reynolds number () in turbulent TC flows (Huisman et al 2014), where only one flow state is expected.…”
Section: Introductionmentioning
confidence: 99%
“…These multiple flow states have recently been found to exist even at extremely high Reynolds number () in turbulent TC flows (Huisman et al 2014), where only one flow state is expected. The reported methods for generating different flow states include continuously adjusting the liquid annulus height using a sliding top plate between the inner and outer cylinders while the inner cylinder keeps rotating (Benjamin 1978 b ; Mansour et al 2016) or adjusting the starting acceleration rate of the inner cylinder (Xiao, Lim & Chew 2002; Martínez-Arias et al 2014). Further investigations showed that for the same liquid annulus height the flow state with larger number of vortices induces larger torque on the inner rotating cylinder, for both moderate (Riecke & Paap 1986; Brauckmann & Eckhardt 2013; Ostilla et al 2013; Martínez-Arias et al 2014) and very high (Huisman et al 2014).…”
Section: Introductionmentioning
confidence: 99%